The podcast as the centre of young Colombians' information consumption in the digital sonosphere. - Barrios-Rubio, Andrés (Radio Journal: International Studies in Broadcast & Audio Media, 2025)
The relationship between the sound industry and its audience is influenced by the widespread use of smartphones as the primary means of accessing the internet. This has led to a transformation in media logics, particularly among young people in Colombia, as they adapt to an evolving ecosystem that is redefining the creation, production and distribution of media. The objective of this research is to determine the significance of podcasts in the information consumption habits of listeners/users and to examine how this digital innovation is positioned in the content offer of radio and independent producers. The study employs a mixed methodological approach, including a case study that involves the administration of 190 surveys to young people, the review and listening of digital repositories of podcast platforms and the conducting of fifteen interviews with podcast producers. The main conclusion drawn is that podcasts are revitalizing audio content on-screen, connecting young people with information and the reality of their environment.